Instructions for planning emergency shelters and open spaces in China: Lessons from global experiences and expertise (2020)
Emergency shelters and open spaces play dual roles in providing locations for temporary accommodation and rescue activities during disaster situations. Over time, research has attempted to optimize site selection and design for emergency shelters and open spaces, though they rarely offered lessons to guide actual projects. In this regard, it is paramount to design emergency shelters or open spaces in a forward-looking and dynamic manner, especially when the country faces challenges due to extreme events (e.g. earthquake and floods) and large populations. The aim of this paper is to analyze the issues of this field in China while summarizing instructions for future construction based on the experience and expertise of other countries. Specific suggestions include: (1) combining the designs and plans of emergency shelters/open spaces into the construction of a resilient urban system; (2) embedding routine preparedness into disaster risk reduction approaches; (3) optimizing issues in site-selection using spatiotemporal patterns in refuge demand while designing the shelter system into a hierarchical structure; (4) shifting from a top-down approach to a bottom-up approach, which includes the participation of multiple aspects of shelter construction; and (5) designing and establishing emergency shelters/open spaces to fight against different types of disasters.